Plaque pH changes following consumption of two types of plain and bulky bread - Shiva Mortazavi; Sogol Noin (Wolters Kluwer Medknow Publications, 2011)
Background: Consistency, backing process and content differences could influence cariogenic potential of foods. The aim was to compare plaque pH changes following consumption of two types of bread with different physical characteristics. Methods : In this clinical trial, interproximal plaque pH of 10 volunteers with high risk of dental caries (saliva Streptococcus mutans > 10 5 , high dental caries experience, and average DMFT =6.10 ± 1.56) was measured. Plain traditionally backed "Sangak bread" and soft bulky "Baguette bread" and %10 sucrose solution were tested in a cross over designed experiment. Baseline plaque pH was recorded and followed by 1, 5, 10, 15, 20, and 30 minutes intervals. Data was analyzed using ANOVA and Tukey test (α = 0.05). Results: Sucrose solution caused the most pronounced pH and ∆pH drop from 7.15 ± 0.33 at baseline to 6.78 ± 0.29. Means plaque pH of 10% sucrose solution and Baguette were not statistically different at 1, 20 and 30 minutes (P > 0.05). Mean plaque pH of Sangak and Baguette showed significant differences at 0, 1, 20 and30 minutes (P < 0.05). Sucrose solution caused a dramatic plaque pH drop during first 10 minutes and then within 30 minutes returned to baseline pH. For two bread samples within first 10 minutes, pH increased and then started to decrease during tenth to fifteenth minutes. Conclusion: During all experiment phases, the mean pH of Baguette with less consistency and carbohydrate content and higher rate of starch gelatination was lower compared to Sangak.